2005
DOI: 10.1002/pits.20108
|View full text |Cite
|
Sign up to set email alerts
|

The status of Functional Behavioral Assessment (FBA): Adherence to standard practice in FBA methodology

Abstract: The application of functional behavioral assessment (FBA) has become increasingly visible in school settings since its inclusion in the 1997 reauthorization of the Individuals with Disabilities Education Act. Despite the mandate for FBAs within the educational program of students with disabilities displaying behavior problems, the federal government put forth guidelines that made what constituted an FBA subject to interpretation. Many states have assumed the responsibility of establishing policy for completing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Within the public education system, for example, Weber et al . () found that a majority of the 50 states have established resources for completing IDEA‐mandated functional behaviour assessment, but with substantial variation among state education agencies in terms of which assessment components are included. In fact, the fewest number of agencies were shown to provide any resources on reinforcer identification procedures (seven states) and experimental analyses (11 states).…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Within the public education system, for example, Weber et al . () found that a majority of the 50 states have established resources for completing IDEA‐mandated functional behaviour assessment, but with substantial variation among state education agencies in terms of which assessment components are included. In fact, the fewest number of agencies were shown to provide any resources on reinforcer identification procedures (seven states) and experimental analyses (11 states).…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…The Direct Observation Form (DOF; Achenbach, 1986) and the Student Observation System (SOS; Reynolds & Kamphaus, 2004) are both well-standardized observational systems that can be used for assessing children's behavior in the classroom. Functional behavior assessment is often used within the context of applied behavior analysis, with the idea of identifying the causes of the maladaptive behavior before designing an intervention to change the behavior (Weber et al, 2005). Depending on the target problem and the resources available for the assessment procedures, structured observations can be a useful part of evidence-based assessment.…”
Section: Assessments With Multiple Methodologiesmentioning
confidence: 99%
“…Slightly more than half of the BIPs included positive-based supports while others utilized punitive and aversive procedures. Weber et al (2005) attempted to examine the state-provided FBA and BIP materials for all 50 SEAs in the USA. Their research discovered written resources for completing an FBA from 41 of the 50 SEAs.…”
Section: Addressing the Barriersmentioning
confidence: 99%
“…Focus on school-based teams to implement FBAs and BIPs, along with designs for creating standard practices in FBA methodology, account for much of the recent research (e.g., Scott et al 2005;Weber et al 2005). Guidelines provided by current researchers for future investigation in FBA include a focus on the need for support after teachers receive FBA and BIP training, and bridging the gap between research and practice (Murdock et al 2005;Scott et al 2005).…”
Section: Introductionmentioning
confidence: 97%